The 3rd AGILE Terrestrial Gamma Ray Flash Catalog. Part I: Association to Lightning Sferics. Issue 11 (10th June 2020) - Lindanger, A.; Marisaldi, M.; Maiorana, C.; Sarria, D.; Albrechtsen, K.; Østgaard, N.; Galli, M.; Ursi, A.; Labanti, C.; Tavani, M.; Pittori, C.; Verrecchia, F.
Abstract: We present a complete and systematic search for terrestrial gamma‐ray flashes (TGFs), detected by AGILE, that are associated with radio sferics detected by the World Wide Lightning Location Network (WWLLN) in the period February 2009 to September 2018. The search algorithms and characteristics of these new TGFs will be presented and discussed. The number of WWLLN identified (WI) TGFs shows that previous TGF selection criteria needs to be reviewed as they do not identify all the WI TGFs in the data set. In this analysis we confirm with an independent data set that WI TGFs tend to have shorter time duration than TGFs without a WWLLN match. TGFs occurs more often on coastal and ocean regions compared to the distribution of lightning activity. Several multipulse TGFs were identified and their WWLLN match are always associated with the last gamma‐ray pulse. We also present the first Terrestrial Electron Beam detected by AGILE. This data set together with the TGF sample identified by selection criteria (companion paper Maiorana et al., 2020) constitute the 3rd AGILE TGF catalog. Key Points: A sample of 592 AGILE detected TGFs associated to lightning sferics is presented TGF duration, geographic dependence of the TGF/lightning ratio, and multipulse TGFs are discussed The first Terrestrial Electron Beam detected by AGILE is presented